2022
DOI: 10.1002/jcp.30832
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic roles of evolutionarily conserved signaling intermediate in toll pathway (ECSIT) in pathophysiology

Abstract: The evolutionarily conserved signaling intermediate in toll pathway (ECSIT) is a cytosolic adaptor protein associated with the toll‐like receptor pathway. It has a distinct N‐terminal mitochondrial targeting sequence, pentatricopeptide repeat motif, and a C‐terminal pleckstrin homology domain. ECSIT regulates many biological processes like embryonic development, inflammation, cardiac function, and assembly of mitochondrial complex I. Besides, ECSIT also interacts with multiple signaling intermediates like tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Other biochemical reactions, such as nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) complexes and uncoupled nitric oxide synthase reactions at the meantime also generate certain amounts of non-m ROS, especially in phagocytic cells, including macrophages, DCs, and neutrophils ( 18 20 ). Studies have shown that the activation of TLRs in innate immune cells sends signals via tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) and evolutionarily conserved signaling intermediate in toll pathways (ECSIT), leading to the phagocytosis of mitochondria and eventually contributing to mROS production ( 21 ). The NLR family, another class of cytoplasmic PRRs, also potentially increases mROS levels upon its activation through downstream regulators, such as NLRP3 inflammasomes and NLRX1 ( 22 ).…”
Section: Mitochondria In Initiation and Transduction Of Innate Immune...mentioning
confidence: 99%
“…Other biochemical reactions, such as nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) complexes and uncoupled nitric oxide synthase reactions at the meantime also generate certain amounts of non-m ROS, especially in phagocytic cells, including macrophages, DCs, and neutrophils ( 18 20 ). Studies have shown that the activation of TLRs in innate immune cells sends signals via tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) and evolutionarily conserved signaling intermediate in toll pathways (ECSIT), leading to the phagocytosis of mitochondria and eventually contributing to mROS production ( 21 ). The NLR family, another class of cytoplasmic PRRs, also potentially increases mROS levels upon its activation through downstream regulators, such as NLRP3 inflammasomes and NLRX1 ( 22 ).…”
Section: Mitochondria In Initiation and Transduction Of Innate Immune...mentioning
confidence: 99%